Geekerella : a novel - Poston, Ashley (Quirk Books, 2017)
In a modern version of "Cinderella," geek girl Elle Wittimer enters a cosplay contest behind her stepmother's back and meets teen actor Darien Freeman at a convention cosplay ball.